The Effect of Audit Opinion, Reputation of Kap, Auditors and Audit Committee on the Timeliness of Financial Reports - Eka Sariningsih; Yuliana Yuliana; Iing Lukman; Hani Safitri (Komunitas Dosen Indonesia, 2023)
The purpose of this study is to examine the impact of audit opinions, the reputation of KAPs, auditors, and audit committees on the timeliness of financial reporting in manufacturing companies in the basic and chemical industrial sectors listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. in this study the sampling technique used purposive sampling. The sample for this research is 135 data from 45 manufacturing companies in the basic and chemical industry sectors that are registered and submitting financial reports on the IDX for the 2019-2021 period. The analysis technique for testing is logistic regression. The finding is reveal that audit opinion, and KAP reputation has a positive and significant effect on the timeliness of financial reporting, while the auditor and audit committee have no significant effect on the timeliness of financial reports.